2004
DOI: 10.1055/s-2004-826049
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Appearance of Dysplasia in Ulcerative Colitis and the Role of Staining

Abstract: Objectives Cancer Risk and SurveillancePatients with longstanding extensive ulcerative colitis are at increased risk of developing colorectal cancer. Colonoscopic surveillance is recommended by most authorities in an attempt to reduce the associated mortality. Surveillance relies on the detection of premalignant dysplastic tissue, and where dysplasia is detected, proctocolectomy has historically been and currently remains the management of choice, although there is increasing evidence that adenoma-like dysplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 9 publications
2
36
0
2
Order By: Relevance
“…In recent years, several studies have shown that chromoendoscopy (CE) is more accurate in detecting dysplasia in patients with long-standing inflammatory bowel disease (IBD) [1][2][3][4][5][6][7][8][9] than is conventional endoscopy. In fact, a recent consensus guideline endorsed the use of CE as the standard detection method in this subset of patients.…”
mentioning
confidence: 99%
“…In recent years, several studies have shown that chromoendoscopy (CE) is more accurate in detecting dysplasia in patients with long-standing inflammatory bowel disease (IBD) [1][2][3][4][5][6][7][8][9] than is conventional endoscopy. In fact, a recent consensus guideline endorsed the use of CE as the standard detection method in this subset of patients.…”
mentioning
confidence: 99%
“…In contrast to sporadic CRC, in which the premalignant dysplastic lesion is often a macroscopically visible adenoma, dysplasia in IBD may occur as a subtle mucosal irregularity. 93 These lesions may be plaque-like, irregularly raised areas, verrucous lesions, or a combination of any of the above morphology. 94 It is known that small, flat, or depressed dysplastic lesions may be endoscopically invisible in 50% to 80%.…”
Section: Crc Surveillancementioning
confidence: 99%
“…Three classes of dyes used for chromoendoscopy are mainly differentiated. 7,8 (C) Virtual chromoendoscopy using i-scan highlights the overall appearance of the lesion (arrow). (D) A spraying catheter is advanced and intravital staining with methylene blue is applied using a spraying catheter (arrow).…”
Section: Chromoendoscopymentioning
confidence: 99%